THE EFFECT OF PLANT THERAPY ON THE LEVEL OF LONELY ELDERLY AT THE WREDA HOUSE - Maya Cobalt Angio Septianingtyas; Vivi Sovianti; Arni Nur Rahmawati (Universitas Airlangga, 2023)
ABSTRACT Introduction: The elderly experience changes in physical, biological and psychological functions. This decreased function affects mobility and relationships with other people so that the elderly often experience loneliness, or alone. Efforts to overcome the problem of loneliness in the elderly require planting therapy with an emotional and psychological approach. The purpose of this study was to determine whether there was an effect of planting therapy on the loneliness level of the elderly at the